Endothelial Features Along the Pulmonary Vascular Tree in Chronic Thromboembolic Pulmonary Hypertension: Distinctive or Shared Facets? - Janne Verhaegen; Lynn Willems; Allard Wagenaar; Ruben Spreuwers; Nessrine Dahdah; Lucia Aversa; Tom Verbelen; Marion Delcroix; Rozenn Quarck (Pulmonary Circulation, 2025)
ABSTRACT Chronic thromboembolic pulmonary hypertension (CTEPH) is a rare complication of pulmonary embolism, characterized by the presence of organized fibro‐thrombotic material that partially or fully obstructs the lumen of large pulmonary arteries, microvasculopathy, and enlargement of the bronchial systemic vessels. The precise mechanisms underlying CTEPH remain unclear. However, defective angiogenesis and altered pulmonary arterial endothelial cell (PAEC) function may contribute to disease progression. Despite the observation of differences in histological features, shear stress and ischemia along the pulmonary vascular tree, the potential contribution of PAEC phenotype and function to these disparate aspects remains unexplored. Based on these observations, we postulated that angiogenic capacities and endothelial barrier function may contribute to disparities in histological features observed along the pulmonary vascular tree. We thus explored the histological characteristics of the pulmonary vascular tree using pulmonary arterial lesions obtained during pulmonary endarterectomy (PEA). We focused on the angiogenic vascular endothelial growth factor (VEGF)‐A/VEGF receptor‐2 (VEGFR2) axis and collagen 15A1 (COL15A1), a potential marker of endothelial cells of the systemic circulation. Concurrently, we examined In Vitro angiogenic properties and barrier function of PAECs derived from large and (sub)‐segmental pulmonary arterial lesions. (Sub)‐segmental pulmonary arterial lesions were abundantly recanalized by neovessels, paralleled by an enriched expression of VEGFR2. VEGF‐A expression was more pronounced in large pulmonary arterial lesions. Nevertheless, no significant difference was discerned in In Vitro angiogenic capacities and barrier integrity of PAECs isolated from large and (sub)‐segmental pulmonary arterial lesions. Importantly, our findings revealed the presence of endothelial cells (CD31+) expressing COL15A1, as well as CD31+ cells that did not express COL15A1. This suggests that endothelial cells from both systemic and pulmonary circulation contribute to lesion recanalization. Despite disparate in situ angiogenic cues in VEGF‐A/VEGFR2 axis between large and (sub)‐segmental pulmonary arterial lesions in CTEPH, In Vitro angiogenic capacities and barrier function remain unaltered.